One-step and large-scale preparation of TiO2/amorphous carbon composites with excellent visible light photocatalytic properties. Issue 70 (11th July 2016) - Sha, Dawei; Wang, Jingjing; Wu, Xiao; Zou, Han; Dai, Yu; Ren, Jie; Chen, Ming; Wu, Yanze; Yan, Xuehua
Abstract : The TiO2 /amorphous carbon composite, with narrower band gap caused by oxygen vacancy, doping carbon and bridging hydroxyls, has good visible light property. In the photodegradating RhB process, hole and superoxide radical are the main active species. Abstract : Poor visible light response and high electron–hole recombination efficiency of TiO2 are main problems which limit its applications. A facile method was developed to prepare reduced TiO2 /amorphous carbon composites with particle sizes of about 10–20 nm, which have good visible light absorption and low band gap energy (1.37 eV). The results show that the composite prepared using 1.5 mmol ascorbic acid at 180 °C has good crystallinity, strong visible light absorption and enhanced catalytic activity. The degradation efficiency of the samples for rhodamine B reaches 90% after 100 min under visible light irradiation.